Three-dimensional acoustic metamaterial Luneburg lenses for broadband and wide-angle underwater ultrasound imaging. (1st November 2022) - Kim, Jung-Woo; Hwang, Gunn; Lee, Seong-Jin; Kim, Sang-Hoon; Wang, Semyung
Abstract: This paper introduces spherical and ellipsoidal metamaterial lenses designed based on the Luneburg lens and transformation optics for underwater ultrasound imaging, which enhances signals over a broadband frequency range and detects objects at a wide-angle. The meta-atoms were analyzed with dispersion curves, equi-frequency contours, and effective acoustic parameters to design the lenses and predict the focusing performance. The three-dimensional lenses made of stainless steel were demonstrated numerically and experimentally in an underwater environment to determine the focal length and full width at half maximum. The spherical lens is omnidirectional. The focal length and the full width at half maximum of the spherical lens are 0 λ and 0.6 λ at 80 kHz, respectively. The ellipsoidal lens is thinner on the x -axis than that of the spherical lens. This lens has broadband properties by achieving the focal length and the full width at half maximum of 1.5 λ to 0 λ and 0.95 λ to 0.59 λ at frequencies between 60 kHz and 160 kHz, respectively. These lenses can potentially be applied to sound navigation ranging or medical transducers, providing the opportunities to view the underwater world with improved resolution at broadband and wide-angle.